MANAJEMEN PENDIDIKAN BERBASIS BUDAYA LOKAL LAMPUNG (Analisis Eksploratif Mencari Basis Filosofis) - Diana, Nirva (Analisis: Jurnal Studi Keislaman, 2012)
Education  is a tool  to  raise  the  degree  and  quality  of  the  nation. Good management is needed to keep educational process continuing. Conventional management is going to silence the world of education in responding to the challenges of time and modernity. In the meantime, Lampung community still has a strongly local culture and it has great potential  to become a major principle  for the implementation  of an ideal  education.  Management  education  based  on  local  culture  is, by  itself,  a  manifestation  of  democratic  education  and  community based (community-based  education). By using methods of descriptive and  phenomenological  approach,  it  is  understood  that  the  culture of Lampung-based management   of education is a necessity for management reform in education, particularly among the Lampongs. In addition, it also has a normative as well as the philosophical foundation rooted in the values of local traditions, as well as the demands of an increasingly democratic era and in the country with a democratic system.